GALERI TANI: LANDSCAPE ARCHITECTURE DENGAN PERMACULTURE DI JAKARTA SELATAN - Stefani, Stefani; Husin, Denny (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The phenomenon of food waste in Indonesia has reached a critical point. Food that is still suitable for consumption ends up as waste is an important issue because there are still no buildings or places that process food waste, so DKI Jakarta occupies the first position in terms of Food Waste. The amount of food waste in DKI Jakarta poses a serious problem because it fills up landfills. In this case, regenerative architecture is a way to restore and improve by processing food waste into fertilizer. The purpose of this design is to process food waste into fertilizer by designing waste treatment, urban farms, galleries, and cafes where the fertilizer can be used to grow plants, fruits, vegetables, and herbs that can be used as raw materials for cafes, and can be sold to local residents. The method for this design uses the permaculture architecture method. Permaculture architecture focuses on system linkages, energy efficiency, local production, and ecological integration. The form of this design is a food waste processing, urban farm, gallery, and cafe. The result of this design is a regenerative ecosystem design with interconnections between functions that produce not only consumption spaces, but also recovery and education spaces. The novelty of this design is the integration of spaces that do not produce final waste and are cyclical through a permaculture architecture approach. Keywords:  architecture; waste; permaculture; regenerative Abstrak Fenomena limbah makanan di Indonesia telah mencapai titik kritis. Makanan yang masih layak konsumsi berakhir sebagai limbah merupakan isu penting dikarenakan masih belum ada bangunan maupun tempat yang mengolah limbah makanan, sehingga DKI Jakarta menduduki posisi pertama dalam hal Food Waste. Banyaknya limbah makanan di DKI Jakarta menimbulkan masalah yang serius karena membuat lahan Tempat Pembuangan Akhir (TPA) menjadi penuh. Dalam hal ini, regeneratif arsitektur merupakan cara untuk memulihkan dan memperbaiki dengan mengolah limbah makanan menjadi pupuk. Tujuan dari perancangan ini adalah untuk mengolah limbah makanan menjadi pupuk dengan merancang pengolahan limbah, urban farm, galeri, dan kafe yang pupuknya dapat digunakan untuk menanam tanaman, buah, sayuran, dan rempah yang bisa digunakan untuk bahan baku kafe, dan bisa dijual ke warga sekitar. Metode untuk perancangan ini menggunakan metode permaculture architecture. Permaculture architecture memfokuskan keterkaitan sistem, efesiensi energi, produksi lokal, dan integrasi ekologis. Wujud dari perancangan ini merupakan pengolahan limbah makanan, urban farm, galeri, dan kafe. Hasil dari perancangan ini adalah desain ekosistem regeneratif dengan interkoneksi antar fungsi yang menghasilkan tidak hanya ruang konsumsi, tetapi juga ruang pemulihan dan edukasi. Kebaruan dari perancangan ini adalah integrasi ruang yang tidak menghasilkan limbah akhir dan bersifat siklus melalui pendekatan permaculture architecture.